JUDGMENT KANTOR URUSAN AGAMA TERHADAP NIKAH USIA MUDA PERSPEKTIF MAQASID SYARI’AH (STUDI KASUS DI KUA KECAMATAN TELUK SEGARA KOTA BENGKULU) - Basil, Sahmul (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
This study raises  the  issue  of judgment KUA officials Segara  bay towards young marriage and  Maqasid  Syariah perspective to judgment KUA officials against young marriage. The purpose of this research is to know. This type of research that is used  in preparing this thesis  is qualitative  data  collection techniques of observation, interviews  and documentation, obtained through  informant interviews  at KUA officials and  local community leaders. After the data  obtained qualitatively analyzed by means of: data reduction (data reduction), presentation of data (data display), and draw conclusions (verification). The results showed that the Gulf KUA officials Segara judgment against young marriage that essentially  passive KUA not pick up the ball means KUA only receives and selects the terms  proposed by the prospective bridegroom and bride age if found lacking as has  been required by the Act No. 1 In 1974, the Syariah perspective Maqasid  Overview  judgment KUA officials against young age of marriage is correct because Islam maintain the benefit of the family in particular and society in general. This is in accordance with the rules of fiqh “Maslahah  Muarsalah” ie assuming that this law is just a tool that the end goal is to create a benefit for mankind. Given madaratnya arising from a young age marriage was a very big influence on domestic and social life, the government reserves the right to make the minimum marriage age limit requirement as stipulated in Law No. marriage 1 of 1974 Article 7 paragraph (1) and KHI Article 15 paragraph (1).